School librarians online: integrated learning beyond the school walls. Issue 7 (24th July 2020) - Burns, Elizabeth
Abstract : Purpose: This study aims to explore preservice school librarians' ability to develop and deliver integrated library lessons under remote teaching and learning conditions. This study will help school library educators identify the preparation required in coursework to effectively implement blended learning practices as well as identify perceived barriers and opportunities for implementing effective remote school library practice. Design/methodology/approach: A participatory action research approach was used to explore online teaching strategies in coursework then implement them in K-12 practice. Findings: The findings include six criteria selected, developed lessons and the analyzed reflections of the preservice candidates. These discussed findings identify trends in developed online inquiry lessons and suggest considerations for school library educators when scaffolding instruction in preparation coursework. Future planning also explores considerations of access and technology instruction prior to practice. Research limitations/implications: The COVID-19 crisis presented a unique challenge ideal for exploration by an educator and candidates in a school librarian preparation program. Using a revised assignment to facilitate a deliberate, authentic experience designed to blend theory and practice (Grossman, 2011), the evidence presented in the sample lessons and participant reflections documents that candidates are able to develop online learning and articulate the American Association of School Librarians Learner Competencies through work samples. According to this brief exploration, this preparation program was able to adapt the requirements of the assignment and prepare candidates to develop quality instructional lessons when online teaching pedagogy was embedded along with scaffolded instruction on collaborative teaching and instructional design. The limitation to this study is that the COVID crisis was accepted as the problem in the participatory action research model. Practical implications: When provided instruction on embedded librarianship models and pedagogy practices of online instruction and scaffolded instruction, school library candidates successfully integrated online K-12 instruction. These instructional supports provided the integration of theory and practice necessary for effective preparation. Additional challenges remain to include considerations of access and student motivation which should be addressed in preparation coursework. Originality/value: Never before have we seen all schools closed and instruction moved online without warning. School library preparation programs must look anew at how well they are preparing school librarians for practice across a variety of circumstances. This study looks at the preparation for online instruction K-12 schools were faced with in Spring 2020.